75.8k views
3 votes
If f(x) = x + 8 and g(x) = –4x – 3, find (f – g)(x).

A. (f – g)(x) = –5x – 11
B. (f – g)(x) = –3x + 5
C. (f – g)(x) = –3x – 5
D. (f – g)(x) = 5x + 11

2 Answers

3 votes

Answer: D

Explanation:

User AnotherGeek
by
6.2k points
3 votes

For this case we have the following functions:

f (x) = x + 8

g (x) = -4x - 3

Subtracting the functions we have:

(f - g) (x) = f (x) - g (x)

(f - g) (x) = (x + 8) - (-4x - 3)

Rewriting:

(f - g) (x) = x + 8 + 4x + 3

(f - g) (x) = 5x + 11

Answer:

D. (f - g) (x) = 5x + 11

User Shenhengbin
by
5.4k points